Demand for Benefit Taxation: Evidence From Public Opinion on Road Financing. (December 2014) - Duncan, Denvil; Graham, John; Nadella, Venkata; Bowers, Ashley; Giroux, Stacey
<x xml:space="preserve">Abstract</x> Rising fuel economy standards for motor vehicles and higher road construction costs, coupled with infrequent adjustments to fuel taxes, have eroded the revenue base for road construction and repairs. We use survey data to determine whether the revenue‐enhancement measures being used by policy makers to address the revenue shortfall reflect the public's preferences regarding the distribution of road financing costs. In particular, we explore whether there is public support for the idea that road financing costs should be distributed in proportion to benefits received from roads; that is, the benefit principle. We find that public support for the benefit‐principle ranges from a low of 5 percent to a high of 34 percent, depending on the definition used. We also find evidence that people who support benefit‐principle financing are more likely to agree that the road mileage user‐fee is fair and also more likely to support revenue sources that satisfy the benefit principle. These findings suggest that a mix of revenue sources that vary in the extent to which they satisfy the benefit principle is a responsive political strategy. They also suggest that the low level of support for benefit‐principle financing is partly responsible for the unpopularity of mileage user‐fees. Policy makers who wish to pursue mileage user‐fees as a replacement for fuel taxes should make an effort to educate voters on the advantages of benefit‐based revenue sources.